Tourism policy of Jordan: the aspects of strategic management - Omoush, Muthana Mohammad; Омоуш, Матана Мохаммад (Харківський національний автомобільно-дорожній університет, 2015)
The development of tourism is one of the perspective directions for many countries. For the Jordanian economy with its developed tourist-recreational centers and unique places that combine signs of antiquity and modernity, the importance of tourism is that it is the rapid circulation of capital with relatively low nvestments, it is an efficient means to modernize infrastructure and create new jobs. The development of the national tourism business contributes to the creation of a special small and medium-sized enterprises, as well as activation and stimulation of work of some economic sectors: construction, trade, transport and communication, agriculture. The efficient tourism policy will allow attracting domestic and inbound tourists, and in the future may lead the regional tourist business to the global level of tourist services. The article deals with perspective directions of development of tourism in Jordan. The tourism potential of Jordan as a major factor in the activation of the tourism business is analyzed. Theoretical and methodological bases of formation and implementation of tourism policy of the state are presented. The main elements and direction of the tourism policy are described. The conceptual model of the implementation of the strategic directions of tourism policy in Jordan is formed. The methods of comparative analysis, analysis and synthesis, as well as the method of induction are used in the article. The results of the study can be used by tourism enterprises in Jordan and state authorities for the formation of the tourism program at the level of enterprises, regions or countries.
Политика туризма в Иордании: аспекты стратегического управления
Keywords: state tourism policy; strategic management; strategic priorities; tourism product; strategy of tourism development; государственная политика туризма; стратегическое управление; стратегические приоритеты; изделие туризма; стратегия развития туризма; 338.48